Remodelling adversely impacts arrhythmic outcome following isolated aortic valve replacement surgery - João Pedro Figueiredo Oliveira (2020)
Background: Atrial fibrillation (AF) is the most common arrhythmia with adverse clinical outcomes. Aortic valve replacement is one of the most frequently performed cardiac surgeries, although there is scarce evidence on arrhythmic outcomes. We aimed to evaluate AF during the first 9 months post- isolated aortic valve replacement surgery and its clinical, analytical and echocardiographic predictors. Methods: 379 severe aortic stenosis patients with no prior atrial fibrillation who underwent isolated aortic valve replacement surgery during two years were included in our study. Logistic regression was used to find independent factors associated with follow-up AF and identify patients at high risk. We performed a comparison between pre- and postoperative echocardiographic data (baseline and follow-up) using paired sample t tests and Wilcoxon sign rank. Results: Postoperative AF (POAF), diabetes, and follow-up indexed left atrium diameter (LAD) were significantly higher in the group of patients developing AF. We found POAF during hospital stay and left atrium diameter at follow-up were independent predictors of AF at follow-up. No differences were found between groups when comparing baseline and follow-up echocardiographic data except for indexed left ventricle end-diastolic diameter (LVED), which failed to decrease after surgery in the AF group, and indexed interventricular septum thickness, which showed a tendency to decrease only in patients remaining in sinus rhythm. Conclusions: POAF and indexed LAD independently predicted AF at 9 months following isolated aortic valve replacement surgery in aortic stenosis patients with no preoperative AF history. LVED diameter did not decrease significantly at follow-up in AF patients, possibly reflecting adverse ventricular remodelling